Literary Landscapes
XXV, 221 p.
Keywords: This book explores the varied ways in which modernist and postcolonial innovations in fiction are motivated by crises and revolutions in the human perception and appropriation of space. 'Space' for the writers concerned has its political, historical, cultural and gender dimensions as well as its geographical identity.